La Politica di Brunetto Latini: Una riscrittura politica del "De Regimine Civitatum" di Giovanni da Viterbo - Napolitano, David Pierangelo Hubert (Reti Medievali Rivista, 2018)
It is generally accepted that the final section of Brunetto Latini’s Li Livres dou Tresor, known as his Politica, is largely based upon Giovanni da Viterbo’s De regimine civitatum. Notwithstanding this agreement on the derivative relationship between both texts, Latini’s Politica continues to puzzle scholars. Based upon a historically informed textual comparison and analysis this article argues that the amount of intervention by Brunetto Latini – and its coherence in direction – is highly instructive on the originality of Latini’s rewriting and indicative of its purpose. Finally, this article sheds light on the historical factors underlying Latini’s decision to select Giovanni da Viterbo’s text.